Rheological properties of Sesbania cannabina galactomannan as a new source of thickening agent. Issue 4 (11th March 2022) - Tao, Yuheng; Ma, Junmei; Huang, Caoxing; Lai, Chenhuan; Ling, Zhe; Yong, Qiang
Abstract : Abstract: The present study evaluated the rheological properties of galactomannan from Sesbania cannabina . The intrinsic viscosity of galactomannan was determined to be 8.63 ± 0.06 dl/g. Moreover, the onset of galactomannan coil overlap occurred at 5.12 ± 0.13 g/L. With increasing concentration, galactomannan showed a more distinct shear‐thinning behavior, which was well characterized by the Cross model. Notably, the viscosity of polysaccharide showed a negative relationship with the temperature, while the activation energy decreased with increasing polysaccharide concentration. Furthermore, at high concentrations, the galactomannan solution showed stability after heating or freezing, as well as over the wide pH range of 5.0‒9.0. Dynamic viscoelasticity measurements reveal a gradual transition from viscous to elastic behavior of galactomannans with an increasing frequency. It is anticipated that S. cannabina galactomannan will find interesting applications as a natural thickener due to the comprehensive description of its rheological properties presented herein. Practical Application: The investigated S. cannabina galactomannan has shown a higher viscosity and heat stability at high concentration, as well as a good stability at the pH range of 5–9. The S. cannabina galactomannan may be employed as stabilizers in the food field.